Quinoline-Benzimidazole Conjugate Based Fluorescent Chemosensor: A Ratiometric Sensor for the Differentiation of Rutile and Anatase TiO2 Nanoparticles - K. Velmurugan; S. Suguna; I. Sheebha; C. Immanuel David; B. Vidhya; J. Prabhu; R. Nandhakumar (New Innovations in Chemistry and Biochemistry Vol. 7, 2022)
A quinoline-benzimidazole conjugate 1 has been synthesized and characterized by the usual spectroscopic and analytical data. The probe is utilized for the discrimination of TiO2 anatase and rutile nanoparticles by the spectrofluorimetry technique as a potential fluorescent chemosensor. Probe 1 exhibits selective TiO2 sensing through a photoinduced electron transfer process (PET) and the ratiometric sensing response by intramolecular charge transfer (ICT) mechanism. A 1:2 binding ratio was arrived with the help of fluorescence titration data of TiO2 rutile and anatase phases with conjugate 1 and the association constant (Ka) of 1+TiO2 anatase and 1+TiO2 rutile were computed to be 6.34 × 104 M-2 and 5.179 × 104 M-2, respectively. The limit of detection of TiO2 nanoparticles by probe 1 was up to micro molar concentrations. The effect of time and pH were also recorded. Hence, the probe 1 can potentially be applied to the environmental and biological samples.